ANALISIS PENERAPAN MODEL PEMBELAJARAN BERBASIS KERJA DI STIPAS KEUSKUPAN AGUNG KUPANG - Taek, Emilia dolorosa; Karan, Yoseph Mikhael Boli (Pastoralia Jurnal Penelitian Dosen, 2022)
The work-based learning model is a learning model that is student-centered, because this learning model is a means or provision that allows students to use the workplace context to learn and apply learning material. STIPAS Archdiocese of Kupang has currently implemented a work-based learning model in certain courses, but it is not well developed, because the learning model only focuses on theory. Meanwhile, by maximizing the work-based learning model, the results and achievement of learning targets can help students who, after graduating, can work in a number of formal sectors according to their skills. The aim of this research is to analyze the application of the work-based learning model so that we can find out the general picture of the use of work-based learning, supporting and inhibiting factors and what efforts need to be made so that this learning model can be optimized, because if this model is used effectively and efficiently then can improve the quality of student learning. The method used in this research is descriptive qualitative, where this method describes a particular situation which is the object of research. With this method, researchers obtained a lot of information regarding the implementation of the work-based learning model at STIPAS KAK. The results found are that the work-based learning model has been implemented well at STIPAS KAK, this can be seen from the results of graduates who have obtained jobs not only as religious teachers but some also work in other fields.